2017
DOI: 10.1038/gt.2017.31
|View full text |Cite
|
Sign up to set email alerts
|

SOST silencing promotes proliferation and invasion and reduces apoptosis of retinoblastoma cells by activating Wnt/β-catenin signaling pathway

Abstract: This study aimed to investigate the effects of SOST and the Wnt/β-catenin signaling pathway on the proliferation, migration, invasion, and apoptosis of human retinoblastoma cells. Fifty-five retinoblastoma and 21 normal retinal tissue samples were collected as the case group and control group, respectively. HXO-RB44 and SO-RB50 cells were selected and assigned into blank, negative control (NC), siRNA 1, siRNA 2, siRNA 3, IWR-1-endo 1, IWR-1-endo 2 and IWR-1-endo 3 groups. Quantitative real-time polymerase chai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 23 publications
3
17
0
Order By: Relevance
“…A previous study demonstrated that OS progression is associated with the transcriptional activity of activated β‐catenin 23 . Besides, some studies have also shown that MMP2 is closely associated with the Wnt/β‐catenin signalling pathway 24‐26 . This study validates that LINC01128 affects MMP2 mRNA stability through competitive binding with miR‐299‐3p.…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…A previous study demonstrated that OS progression is associated with the transcriptional activity of activated β‐catenin 23 . Besides, some studies have also shown that MMP2 is closely associated with the Wnt/β‐catenin signalling pathway 24‐26 . This study validates that LINC01128 affects MMP2 mRNA stability through competitive binding with miR‐299‐3p.…”
Section: Resultssupporting
confidence: 78%
“…23 Besides, some studies have also shown that MMP2 is closely associated with the Wnt/β-catenin signalling pathway. [24][25][26] This study…”
Section: Linc01128 and Mmp2 Jointly Activate The Wnt/β-catenin Signmentioning
confidence: 92%
“…It is therefore plausible that an aberrant increase of FGF10 expression is driving left ventricular cardiomyocyte proliferation in NS-CM. Similarly, the upregulation of EREG and downregulation of FOSB and SOST that we observed in NS-CM have previously been associated with increased cell proliferation in a number of physiological and cancerous processes ( Cao et al., 2013 ; Kyotani et al., 2013 ; Morato et al., 2021 ; Nishioka et al., 2020 ; White et al., 2010 ; Wu et al., 2017 ; Xu et al., 2017 ; Zhang et al., 2020 ; Zou et al., 2017 ). As an upstream component of the Ras-MAPK pathway, the EGFR ligand EREG is a particularly interesting candidate for further studies of the mechanisms of NS-CM.…”
Section: Discussionsupporting
confidence: 80%
“…MMP-2 is a member of the metalloproteinase family, which degrades various components of the extracellular matrix, changes the microenvironment of tumors, and facilitates tumor cell migration [32,33]. The migration of glioma cells is special, and they actively migrate and this is achieved in two ways: through the perivascular space and the brain parenchyma.…”
Section: Discussionmentioning
confidence: 99%